Marketing LIS Education through Departmental (DLIS) Blog: A Proposal to Build Relationship with Public and Professionals - Prasad, M.R. Murali (DESIDOC Journal of Library & Information Technology, 2016)
This paper describes the need of exclusive blog for Department of Library and Information Science (DLIS) in a university to visualise the courses and their syllabi, to showcase the strength of the faculty, to disseminate the LIS research, and to create an online platform to interact with the department authorities, with embedding Web 2.0 tools into their respective blogs. Also, the paper describes the different strategies to develop and sustain a blog for DLIS in a university. Over all this concept of a blog is to create an interactive platform to publicise the LIS education and research to the existing and prospective LIS professionals in the world and particularly in India.